Unraveling Gender Inequality in Pakistan's Political Economy - Munir Ahmad; Saira Bashir; Zahid Hussain; Alyas Ali Chaichi (MultiTech Publisher, 2023)
This study explores the complex relationship between political economy and gender inequality in Pakistan. The study finds a disconnect between progressive legal measures and their successful implementation through a thorough investigation of policy papers, legislative records, and qualitative interviews. The results highlight the critical need for interventions that go beyond legal changes and have both theoretical and practical ramifications. In practical terms, the research suggests multifaceted approaches that take into account political and economic factors, question gender stereotypes, and encourage women's involvement in decision-making. Theoretically, it advances feminist political economy by highlighting the need of including social and cultural aspects in frameworks for economic policy. The main goal of policy interventions should be to establish a supportive atmosphere that promotes equality of opportunities and challenges gender conventions. In order to achieve gender equality in Pakistan, policymakers and practitioners are urged by this study to adopt a holistic plan.